New Insights into the Lpt Machinery for Lipopolysaccharide Transport to the Cell Surface: LptA-LptC Interaction and LptA Stability as Sensors of a Properly Assembled Transenvelope Complex - Sperandeo, Paola (American Society for Microbiology (ASM), 2011)
Lipopolysaccharide (LPS) is a major glycolipid present in the outer membrane (OM) of Gram-negative bacteria. The peculiar permeability barrier of the OM is due to the presence of LPS at the outer leaflet of this membrane that prevents many toxic compounds from entering the cell. In Escherichia coli LPS synthesized inside the cell is first translocated over the inner membrane (IM) by the essential MsbA flippase; then, seven essential Lpt proteins located in the IM (LptBCDF), in the periplasm (LptA), and in the OM (LptDE) are responsible for LPS transport across the periplasmic space and its assembly at the cell surface. The Lpt proteins constitute a transenvelope complex spanning IM and OM that appears to operate as a single device. We show here that in vivo LptA and LptC physically interact, forming a stable complex and, based on the analysis of loss-of-function mutations in LptC, we suggest that the C-terminal region of LptC is implicated in LptA binding. Moreover, we show that defects in Lpt components of either IM or OM result in LptA degradation; thus, LptA abundance in the cell appears to be a marker of properly bridged IM and OM. Collectively, our data support the recently proposed transenvelope model for LPS transport.